2008
DOI: 10.1086/588383
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐Induced Iron‐Acquisition Systems and TonB Contribute to Virulence inKlebsiella pneumoniaeCausing Primary Pyogenic Liver Abscess

Abstract: Iron uptake systems were the genes in K. pneumoniae that were highly up-regulated in response to sera. Although there are multiple iron transporter systems in NTUH-K2044, a mutation in all 3 loci (irp2, iuc, and iroA) is necessary to decrease virulence. The tonB mutant is a potential vaccine candidate because it can induce a significant protective immune response against challenge with a wild-type strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
204
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(217 citation statements)
references
References 38 publications
7
204
6
Order By: Relevance
“…Our previous work demonstrated that PLA strains harbor a pathogenesis-specific genotype and transcriptional profile. 31 We therefore hypothesized that a novel adhesin may be produced in PLA-causing K. pneumoniae. However, our in vitro observations suggested that K. pneumoniae has a broad tissue tropism and can infect various types of human epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work demonstrated that PLA strains harbor a pathogenesis-specific genotype and transcriptional profile. 31 We therefore hypothesized that a novel adhesin may be produced in PLA-causing K. pneumoniae. However, our in vitro observations suggested that K. pneumoniae has a broad tissue tropism and can infect various types of human epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains, plasmids, and primers used in this study are listed in Table S1. 30,31,41,43,51 Gene deletion and complementation. K. pneumoniae mutated in yfgL, clpS, entS, fim, yraM, or pts were constructed using the previously described unmarked deletion method.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations